Influence of Anti-TNF and Disease Modifying Antirheumatic Drugs Therapy on Pulmonary Forced Vital Capacity Associated to Ankylosing Spondylitis: A 2-Year Follow-Up Observational Study - Alberto Daniel Rocha-Muñoz; Aniel Jessica Leticia Brambila-Tapia; María Guadalupe Zavala-Cerna; José Clemente Vásquez-Jiménez; Liliana Faviola De la Cerda-Trujillo; Mónica Vázquez-Del Mercado; Norma Alejandra Rodriguez-Jimenez; Valeria Díaz-Rizo; Viviana Díaz-González; Ernesto German Cardona-Muñoz; Ingrid Patricia Dávalos-Rodríguez; Mario Salazar-Paramo; et al. (Journal of Immunology Research)
Objective. To evaluate the effect of anti-TNF agents plus synthetic disease modifying antirheumatic drugs (DMARDs) versus DMARDs alone for ankylosing spondylitis (AS) with reduced pulmonary function vital capacity (FVC%). Methods. In an observational study, we included AS who had FVC% <80% at baseline. Twenty patients were taking DMARDs and 16 received anti-TNF + DMARDs. Outcome measures: changes in FVC%, BASDAI, BASFI, 6-minute walk test (6MWT), Borg scale after 6MWT, and St. George’s Respiratory Questionnaire at 24 months. Results. Both DMARDs and anti-TNF + DMARDs groups had similar baseline values in FVC%. Significant improvement was achieved with anti-TNF + DMARDs in FVC%, at 24 months, when compared to DMARDs alone (P=0.04). Similarly, patients in anti-TNF + DMARDs group had greater improvement in BASDAI, BASFI, Borg scale, and 6MWT when compared to DMARDs alone. After 2 years of follow-up, 14/16 (87.5%) in the anti-TNF + DMARDs group achieved the primary outcome: FVC% ≥80%, compared with 11/20 (55%) in the DMARDs group (P=0.04). Conclusions. Patients with anti-TNF + DMARDs had a greater improvement in FVC% and cardiopulmonary scales at 24 months compared with DMARDs. This preliminary study supports the fact that anti-TNF agents may offer additional benefits compared to DMARDs in patients with AS who have reduced FVC%.